Photo-Driven Reduction of Carbon Dioxide: A Sustainable Approach Towards Achieving Carbon Neutrality Goal - Gui, Meei Mei; Lee, W.P. Cathie; Putri, Lutfi Kurnianditia; Kong, Xin Ying; Tan, Lling-Lling; Chai, Siang-Piao (Frontiers in Chemical Engineering, 2021)
The photo-driven reduction of carbon dioxide (CO2) into green and valuable solar fuels could be a promising solution to simultaneously address energy- and environmental-related problems. This approach could play an integral role in achieving a sustainable energy economy by closing the carbon cycle and allowing the storage and transportation of intermittent solar energy within the chemical bonds of hydrocarbon molecules. This Perspective discusses the latest technological advancements in photo-driven CO2 conversion via various pathways, namely photocatalysis, photoelectrocatalysis and photovoltaic-integrated systems. In addition to providing an outlook on unresolved issues concerning the said technologies, this Perspective also spotlights new trends and strategies in the structural engineering of materials to meet the demands for prominent CO2 photoreduction activity as well as spearhead the ground-breaking advances in the field that lead to the translation of CO2 photo-driven technologies from the laboratory to industrial-scale applications.